Effect of external heat source on temperature and moisture variation for composting of food waste - Jessie, Rose; Jia Chi, Lai; Yi Lung, Then; Chamath Kanalaka, Vithanawasam (IOP Publishing Ltd., 2021)
This paper investigates the outcome of having an external heat source on temperature and moisture variations in the food waste composting process. Food waste accumulation is a growing concern in many countries. Converting food waste into usable compost is a more desirable tactic than dumping to crowded landfill sites. Closed composting was applied in this work, which relies on a controlled but uninterrupted airflow during the organic material degradation process. However, undesirable odour released at low aeration rate due to low temperature and high moisture content found in the compost. Finding the ideal aeration rate with the least possible loss of moisture is needed, which was discussed in this paper. The vegetable-fruit waste used in the experiment was given an aeration rate of 0.3 L/min at a moisture setting of 60% and 70%. For 15 mins/day, the forced aeration was carried out at 3-day intervals. Results showed that 0.3 L/min with 60% and 70% moisture content attained best temperature peaks of 32.4°C and 31.6°C, respectively at day 13 for 28 days composting. A strong odour continued to exist with the compost and was mitigated by using an external additional heat source (light bulb). The light bulb also helped to provide a higher temperature for the compost of 41.5°C by day 1 for 10 days composting.